7 - Le désordre du monde - Ndiaye, Babacar (Africa Development, 2021)
The beginning of the twenty-first century is characterized by the exponential accumulation succession of serious events: crises, indiscriminate terrorist acts and wars. Void of any pessimism or complacency, this article constitutes the foundation of a critical analysis of the situation prevailing in the world. This deeply resembles disorder. Beyond this acknowledgement, and as a simple con- tribution, some indicative tracks are explored for the elimination of this world disorder.